THE IMPLEMENTATION OF SELF ASSESSMENT THROUGH READING ACTIVITY TO STIMULATE STUDENT’S METACOGNITIVE SKILL - Yasri, Hayyun Lathifaty; Sari, Sulistya Umie Ruhmana (Proceeding of International Conference on Islamic Education (ICIED); Vol 3 No 1 (2018): Proceeding of International Conference on Islamic Education (ICIED), 2018)
This research aims to highlights the effect of applying the 10 minutes reading activity before the instructional process to stimulate student self-assessment for enhancing student's metacognitive skill. The researcher uses a quasi-experiment method with the subject is a student of Social Science Education in Tarbiyah Faculty of UIN Maulana Malik Ibrahim Malang. The subject of this research was taken by purposive sampling technique. The data were collected by questionnaire of student metacognitive improvement. So, the data were analysed by t-test at a sign. 0.05. The finding of this research shown that student's metacognitive skill in experimental class is higher than student metacognitive skill in control class. It was approved by the student's metacognitive skill score in experimental class improvement from 76 to 89, and student's metacognitive skill score in the control class from 76 to 80. It can be concluded that student's metacognitive skill improvement in the experimental class is higher than the student's metacognitive skill in the control class so that student's self-assessment is effective to enhance student's metacognitive skill.